Tax control of the commune and its consequences - Dolewka, Zofia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of the article is an attempt to outline the boundaries of taxation powers of communes and to indicate their influence on the amount of budget revenues. The research method was the analysis of literature, applicable law acts and data relating to budget revenue resulting from the power of taxation and their relationship to own revenue and total revenue. The study includes a thesis that local authorities can create local tax policies (on the basis of their powers), but in its essence it slightly affects the execution of budget revenues of communes. The rights of taxation powers granted to communes are systematically used by the government authorities. Generally, applying lower tax rates or exemptions in question affects the reduction of budget revenues of communes. Thus, consequences of using power of taxation may be defined as so-called lost income. The observations have made it possible to formulate the assumption that municipalities usually use these powers to reduce the higher tax rates
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 127-137
Keywords: commune; budget; financial autonomy; tax controlling; gmina; budżet; samodzielność dochodowa; władztwo podatkowe